RETICULARIA M'COY y LEIORHYNCHUS HALL (BRACHIOPODA) EN LA FORMACIÓN PITUIL, CARBONÍFERO SUPERIOR, PROVINCIA DE SAN JUAN (Ameghiniana, 2014)
Reticularia notica Reed, 1927 and Leiorhynchus sp. nov.? from the Pituil Formation are described and figured. Both species belong to the Balakhonia peregrina-Geniculifera tenuicostata Zone of late Westphalian age.